Genetic Variation in the IL-6 and HLA-DQB1 Genes Is Associated with Spontaneous Clearance of Hepatitis C Virus Infection. (2nd June 2016) - Waldron, Paul Ravi; Belitskaya-Lévy, Ilana; Chary, Aarthi; Won, Johann; Winters, Mark; Monto, Alexander; Ryan, James; Lazzeroni, Laura C.; Holodniy, Mark
Abstract : Background . Millions of people are infected with hepatitis C virus (HCV) worldwide and 30% spontaneously clear the infection. Reasons for HCV clearance without antiviral treatment are not well understood. Methods . Blood was collected for DNA analysis from patients with chronic HCV infection or evidence of spontaneous clearance. To overcome anticipated limitations of small sample size, primary analyses consisted of a candidate gene analysis of 12 preselected genes based on known association with host immunologic response to HCV infection. To further reduce the impact of multiple testing on power, a single likelihood ratio test was conducted for each gene using all associated SNPs assayed on the Illumina Quad 610/660W chip. Step-down permutation methods were used to adjust for multiple testing in all analyses. Results . Ninety-five and 62 patients with HCV chronic infection or spontaneous clearance, respectively, were included for analysis. HLA-DQB1 (p = 1.76 ⁎ 10 - 5 ) and IL-6 (p = 0.0007 ) genes were significantly associated with spontaneous HCV clearance. IL-28B was not significantly associated with spontaneous clearance (p = 0.17 ). Conclusion . Our whole-gene analytic strategy identified a previously unreported association of IL-6 with spontaneous clearance of HCV infection. We also confirmed the finding that HLA-DQB1 is associated with spontaneous resolution of HCV infection.